Širša perspektiva vpogleda v ustreznost bolnikovega bivalnega okolja - socialno delo na terenu - Skok, Vanja (Rehabilitacija (Ljubljana), 2015)
The aim of social work in rehabilitation is solving social problems relevant to the person undergoing rehabilitation, as well as cooperation within a multidisciplinary team that plans and implements the programs of comprehensive rehabilitation. Social work is aimed to support patients - goals and decisions. The living environment of the patient after discharge dictates the form and the selection of professional intervention. Planning of discharge is an important part of social treatment and is carried out with an individualised approach, which enables selection of adequate forms of support. The social treatment must account for objective and subjective factors in the patient's reality, either regarding their influence on rehabilitation or regarding the planning of discharge. Field work is an important part of social work in rehabilitation of persons with spinal cord lesions. Social work is always carried out within the context of a certain environment and is a process of interaction with people in that environment. Field work takes the social worker outside the boundaries of his or her workplace in the institution and into the institutional place of other services and professionals who cooperate with the social worker in performing the tasks. By visiting the patient at his or her home, the social worker enters the patient's living environment in a direct and interactive manner.
Keywords: Environment; field work; health care services; natural environment; okolje; okvara hrbtenjače; Social Work; socialno delo; Spinal Cord Compression; terensko delo; zdravstvena dejavnost